The Impact of Changes in Environmental Conditions on Organic Acid Production by Commercial Wine Yeast Strains - Chidi, B.S.; Bauer, F.F.; Rossouw, D. (South African Journal of Enology and Viticulture, 2018)
Acidity is one of the primary sensory elements in wine, and the balance of sugar and acidity is probably the strongest element affecting wine appreciation. However, little is known about how yeast strains and fermentation conditions will affect the production of fermentation-derived acids, including acetic, succinic and pyruvic acid. This study employs a multifactorial experimental design to provide a better understanding of how individual or simultaneous changes in environmental parameters such as pH, sugar and temperature influence the production of individual organic acids during fermentation in several yeast strains in synthetic must. Certain changes in environmental factors led to conserved trends between strains and treatments. Strains produced higher succinic acid levels when temperature was increased. Significant strain-dependent differences were observed when sugar concentrations were varied for both strains: the combinatorial impact of high initial sugars and fermentation temperature was more pronounced when increased pyruvic acid production was observed in yeast strain VIN13. On the other hand, while combinatorial influences are evident, higher sugar fermentation settings were largely characterised by high acetic acid concentrations for both strains. It is clear that simultaneous changes in sugar, pH and temperature affect organic acid trends in a variable manner, depending on the particular combination of environmental parameters and yeast strain. The study provides valuable information regarding the manner in which initial must parameters and environmental conditions throughout fermentation may affect wine acidity. Since many of these parameters can be controlled at least in part during the winemaking process, the data provide important background information for oenological strategies that aim to optimise the acid balance of wines.